2001
DOI: 10.1897/1551-5028(2001)020<0133:aoehim>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Estrogenic Hormones in Municipal Wastewater Effluent and Surface Water Using Enzyme-Linked Immunosorbent Assay and Gas Chromatography/Tandem Mass Spectrometry

Abstract: Although the estrogenic hormones 17 beta-estradiol and 17 alpha-ethinyl estradiol can be quantified in polluted waters by gas chromatography/mass spectrometry (GC/MS) and gas chromatography/tandem mass spectrometry (GC/MS/MS), the compounds often are present at concentrations below detection limits. Enzyme-linked immunosorbent assays (ELISAs) provide a sensitive and robust means of quantifying estrogenic hormones in wastewater effluents and surface waters. Results from ELISA analysis of estrogenic hormones in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
111
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(117 citation statements)
references
References 14 publications
5
111
0
1
Order By: Relevance
“…Numerous procedures can disturb the fate and means of transport of carbon-based complexes in the environment, including sorption, biotic alteration, and abiotic alteration [27][28][29][30]. Information about chemical properties and structures of complexes can allow for initial approximation of their fate and persistence.…”
Section: Fate and Occurrence Of Antibiotics In The Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous procedures can disturb the fate and means of transport of carbon-based complexes in the environment, including sorption, biotic alteration, and abiotic alteration [27][28][29][30]. Information about chemical properties and structures of complexes can allow for initial approximation of their fate and persistence.…”
Section: Fate and Occurrence Of Antibiotics In The Environmentmentioning
confidence: 99%
“…Information about chemical properties and structures of complexes can allow for initial approximation of their fate and persistence. The persistence and movement of antibiotics in the ecosystem have been determined as: sulfonamides and fl uoroquinolones are the most persistent, followed by macrolides; tetracyclines can persist for comparatively extensive ages in the absence of sunlight [27]. Tetracyclines and fl uoroquinolones are easily adsorbed by soils, sediments, and/or manure slurry [2,31].…”
Section: Fate and Occurrence Of Antibiotics In The Environmentmentioning
confidence: 99%
“…As an alternative for assay of environmental pollutants in water, immunoassay has the merits of low cost, high throughput, direct sample testing, and small sample volume (submilliliter to microliter) (17,(21)(22)(23)(24)(25)(26)(27). Although currently available enzyme-linked immunosorbent assay (ELISA) methods were for individual SAs in waters (17,28), it should be possible to screen a broad spectrum of SAs in environmental waters by ELISA with antibodies that have a broadspecificity for SAs (29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations were extremely low, and close to or even below the detection limits available at the time, but nevertheless they were high enough to cause effects. Subsequent studies in other countries confirmed these results (e.g., Huang and Sedlak [9]). …”
Section: Answering the Important Challengesmentioning
confidence: 64%
“…It would be difficult to think of a more environmentally relevant parameter than reproduction when attempting 2084 All Supplemental Data may be found in the online version of this article. See Table S1 for the number of citations and rank of all the ''Top 100'' papers, which in this essay are references [3][4][5][6][7][9][10][11][12][13][14][15]19,20].…”
Section: Answering the Important Challengesmentioning
confidence: 99%